2012
DOI: 10.1172/jci58976
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A overcomes cancer hypoxia and metastatic dissemination induced by antiangiogenic treatment in mice

Abstract: Cancer development, progression, and metastasis are highly dependent on angiogenesis. The use of antiangiogenic drugs has been proposed as a novel strategy to interfere with tumor growth, but cancer cells respond by developing strategies to escape these treatments. In particular, animal models show that antiangiogenic drugs currently used in clinical settings reduce tumor tissue oxygenation and trigger molecular events that foster cancer resistance to therapy. Here, we show that semaphorin 3A (Sema3A) expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
149
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 50 publications
9
149
1
Order By: Relevance
“…Effect of sunitinib on survival ( ÃÃÃÃ , P < 0.0001; right). B, animals (10 per group) were killed with a median primary tumor of 2 Â 10 5 PC (tumor weight $1 g) on different days (median vehicle 19 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26); sunitinib 32 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and lung metastases were assessed by BLI (mean AE SEM). Primary tumor (PC; left); lung metastatic burden (PC; right) at scheduled death (mean AE SEM; Ã , P < 0.05).…”
Section: The Increase In Metastases Due To Sunitinib Depends On Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of sunitinib on survival ( ÃÃÃÃ , P < 0.0001; right). B, animals (10 per group) were killed with a median primary tumor of 2 Â 10 5 PC (tumor weight $1 g) on different days (median vehicle 19 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26); sunitinib 32 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and lung metastases were assessed by BLI (mean AE SEM). Primary tumor (PC; left); lung metastatic burden (PC; right) at scheduled death (mean AE SEM; Ã , P < 0.05).…”
Section: The Increase In Metastases Due To Sunitinib Depends On Tumormentioning
confidence: 99%
“…In some studies, antiangiogenic therapy was extremely effective on the primary tumor and metastasis, improving survival (13)(14)(15). However, surprisingly, recent studies reported that treatment of tumor-bearing mice, mainly with anti-VEGF/VEGFR-related compounds, increased tumor invasiveness and metastasis (16)(17)(18)(19)(20)(21)(22). Clinical data on the effect of antiangiogenesis in general, or anti-VEGF therapy, on malignant progression are lacking and widely debated.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to anti-VEGF therapy develops by activation of alternate proangiogenic pathways, likely in response to increased tumor tissue hypoxia. In preclinical studies, when angiogenesis is impaired, tumor mass shrinks initially, followed by enhanced tumor invasiveness and metastasis [14] .…”
Section: Introductionmentioning
confidence: 99%
“…8). These results pointed out that the enhanced antitumor activity observed for the CKAAKNfunctionalized squalene-gemcitabine nanoparticles reflects by the multiple ability of (i) targeting both tumor and vessel cells, (ii) inhibiting tumor growth and angiogenesis and (iii) normalizing the vasculature [51,52] (Fig. 9).…”
Section: Antitumor Efficacy Of Ckaakn-functionalized Nps In Rip-tag2mentioning
confidence: 86%
“…RIP-Tag2 mice offer the advantage of both a spontaneous tumor development through multistage tumorigenesis and a well-documented angiogenic switching, in parallel to cancer progression. This well-characterized mouse model represents a suitable and highly reproducible platform to perform pre-clinical trials to test the effects of and anti-tumor and anti-angiogenic drug [28,[48][49][50][51][52]. In this work we used RIP-Tag2 mice as proof-of-concept model to assess the ability of SQdFdC/SQCKAAKN NPs to impair tumor angiogenesis and, at the same time, to regress the growth of established cancers, Twelve week-old tumor-bearing RIP-Tag2 mice were injected intravenously (days 0, 3, 7 and 11) with either dFdC (15 mg/kg), SQdFdC NPs (15 mg/kg eq.…”
Section: Antitumor Efficacy Of Ckaakn-functionalized Nps In Rip-tag2mentioning
confidence: 99%